Genre trouble and extreme cinema : film theory at the fringes of contemporary art cinema - Bordun, Troy (Palgrave Macmillan, 2020)
Contents of book: Introduction: Genre Trouble and Extreme Cinema; Carlos Reygadas, the Avant-Garde, and the Senses; Que Viva México!: Reygadas as Documentarian; I Don’t Know It When I See It: Catherine Breillat’s Pornography ; Horrible Pornography: Fat Girl (À Ma Soeur!, 2001); On-Screen and Off-Screen Flesh and Blood: Performance, Pornography, Spectatorship; Reframing Spectatorship Theory with Extreme Cinema; Conclusion: Know Genre, No Trouble